Tinjauan Fiqh Siyasah Terhadap Koruptor Yang Ingin Kembali Menjadi Pejabat - Riski Ayunda; Nadhila Safira; Sitorus, Senny Kristina Putri; Mehnaj Ayuda; Rimbun, Zulfirmansyah (Tabayyun : Journal Of Islamic Studies, 2024)
Various efforts have been made to prevent corruption crimes, but they are still happening by certain individuals and institutions. Several former corruption convicts plan to register to become part of the legislature, including the DPR, DPRD, and DPD in the 2024 elections. Corruption can have a significant impact on society, politics, and the country's economy. Fiqh Siyasah's views related to former corruptors who want to return to office are discussed in this context. However, Article 240 Paragraph 1 letter g of Law Number 7 of 2017 concerning General Elections does not prevent former corruptors from fighting in the General Election.